2010 IEEE 24th International Conference on Advanced Information Networking and Applications Workshops 2010
DOI: 10.1109/waina.2010.197
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Channel Coding and Modulation Scheme Selection for Achieving High Throughput in Wireless Networks

Abstract: Modern wireless communication demands reliable data communication at high throughput in severe channel conditions like narrowband interference, frequency selective fading due to multipath and attenuation of high frequencies. Traditional single carrier systems address this set of problems by the use of complex, computationally intensive equalization filters. The Orthogonal Frequency Division Multiplexing (OFDM) based system, as opposed to single-carrier systems, is considered to be the future of the wireless co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…LPWAN in general and NB-IoT in particular, demand reliable data communication at high throughput in severe channel conditions like narrowband interference, frequency selective fading due to multipath and attenuation of high frequencies [61].…”
Section: Data Rate Enhanced Nb-iot Modulation Selection Schemesmentioning
confidence: 99%
“…LPWAN in general and NB-IoT in particular, demand reliable data communication at high throughput in severe channel conditions like narrowband interference, frequency selective fading due to multipath and attenuation of high frequencies [61].…”
Section: Data Rate Enhanced Nb-iot Modulation Selection Schemesmentioning
confidence: 99%
“…Adaptive channel encoding and code rate is another adaptive technique that has been proposed to select the best encoder or the code rate according to the channel status, as presented in [5][6][7].…”
Section: Adaptive Techniquesmentioning
confidence: 99%
“…In 3GPP standardization, repeating transmission data and the associated control signaling several times has been utilized as a base solution to achieve coverage enhancement for NB-IoT [ 6 ]. However, repeated transmissions come with a multiplicative energy cost as it has been demonstrated by several wireless networks energy consumption modeling studies such as [ 7 , 8 ] which showed that the major contributors to the overall average energy consumption of a wireless network are the energy consumed during transmission as well as the energy consumed during reception. This can be represented as where is the energy consumed by the transceiver circuit on single wireless link, is the transmission power, is the reception power, M is the uplink packet size in bits, B is the transmission bit rate, and is the probability of successful transmission.…”
Section: Introductionmentioning
confidence: 99%